Examining later-in-life health risks associated with sport-related concussion and repetitive head impacts: a systematic review of case-control and cohort studies - Iverson, G. L.; Castellani, R. J.; Cassidy, J. D.; Schneider, G. M.; Schneider, K. J.; Echemendia, R. J.; Bailes, J. E.; Hayden, K. A.; Koerte, I. K.; Manley, G: T.; McNamee, M.; Patricios, J. S.; et al. (British Journal of Sports Medicine, 2023)
Objective: Concern exists about possible problems with later-in-life brain health, such as cognitive impairment, mental health problems and neurological diseases, in former athletes. We examined the future risk for adverse health effects associated with sport-related concussion, or exposure to repetitive head impacts, in former athletes.